STRATEGI KEBERDAYAAN KELOMPOKTANI PADI BERBASIS MODAL SOSIAL DI KECAMATAN KUOK KABUPATEN KAMPAR - Eva Kristi; Ahmad Rifai; Kausar Kausar (Indonesian Journal of Agricultural Economics, 2018)
The purpose of this study was to analyze the relationship of social capital with the empowerment offarmers and the development of strategy to empower rice farmers based on social capital in KuokSubdistrict, Kampar Regency. The research was carried out in Kuok Sub-district, Kampar District,Riau Province, the largest rice producer in Kampar District. Site selection is done intentionally(purposive) with consideration that the research location is one of the areas in Riau Province whichis the center of rice production and has the potential for social capital that can be developed toimprove the welfare of rice farmers through community empowerment. In this study, samplingtechnique was purposive sampling. The main criteria for the sample are rice farmers who aremembers of the farmer group. Data analysis used was rank spearman, and SWOT analysis. Therelationship of social capital and the level of empowerment of lowland rice farmers in Kuok Sub-District, Kampar District has one unidirectional correlation and one direct correlation. The strategyof developing social capital for the level of empowerment of lowland rice farmers in KuokSubdistrict, which are among others is to develop and improve the cooperation of lowland ricefarmers in conducting rice farming, improving the security of the surrounding environment,coaching rice farmers related to eradication of rat pests and coaching rice farmers related to theeradication of bird pests.